Cover Picture: Ann. Phys. 7‐8'2014. Issue 7 (August 2014) - Battye, Richard; Goobar, Ariel; Weller, Jochen
<x xml:space="preserve">Abstract</x> The accelerated expansion of the Universe is now a firmly established observational fact. In recent times, significant progress has been made in measuring the cosmic expansion history and the growth of structures in the Universe with the aim to constrain dark energy models. This issue reviews the state of the art of observational constraints on models of cosmic acceleration and recent progress, and discusses prospects of understanding more about the nature of dark energy. Picture: SKA Organisation/Swinburne Astronomy Productions <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>